Who Can Have Parenteral Antibiotics at Home?: A Prospective Observational Study in Children with Moderate/Severe Cellulitis. Issue 3 (March 2016) - Ibrahim, Laila F.; Hopper, Sandy M.; Babl, Franz E.; Bryant, Penelope A.
Abstract : Background: The benefits of treating children at home or in an ambulatory setting have been well documented. We aimed to describe the characteristics and evaluate the outcomes of children with moderate/severe cellulitis treated at home with intravenous (IV) ceftriaxone via direct referral from the Emergency Department to a hospital-in-the-home (HITH) program. Methods: Patients aged 3 months to 18 years with moderate/severe cellulitis referred from a tertiary pediatric Emergency Department to HITH from September 2012 to January 2014 were prospectively identified. Data collection included demographics, clinical features, microbiological characteristics and outcomes. To ensure home treatment did not result in inferior outcomes, these patients were retrospectively compared with patients who were hospitalized for IV flucloxacillin, the standard-of-care over the same period. The primary outcome was home treatment failure necessitating hospital admission. Secondary outcomes included antibiotic changes, complications, length of stay and cost. Results: Forty-one (28%) patients were treated on HITH and 103 (72%) were hospitalized. Compared with hospitalized patients, HITH patients were older ( P < 0.01) and less likely to have periorbital cellulitis ( P = 0.01) or fever ( P = 0.04). There were no treatment failures under HITH care. The rate of antibiotic changes was similar in both groups (5% vs. 7%, P = 0.67), as was IV antibiotic duration (2.3 vs. 2.5 days, P = 0.23). Conclusion: Older children with moderate/severe limb cellulitis without systemic symptoms can be treated at home. To ascertain if this practice can be applied more widely, a comparative prospective, ideally randomized, study is needed.